Measurement device design: Rain gauge - Sánchez Martos, Antonio J.; Ladrón-de-Guevara-Muñoz, María del Carmen; Ladrón-de-Guevara-López, Isidro; De-Cózar-Macías, Óscar; Blázquez-Parra, Elidia Beatriz (My University, 2018)
The need to size large hydraulic infrastructures, exploit extensive agricultural areas or simply arrange water assets for human consumption makes the evaluation of the available water resources essential. Water is a scarce resource that is poorly distributed both, spatially and temporally. Therefore, a set of hydrological networks that allow the evaluation of water quantity and quality is required. In order to achieve this, the first step is to retrieve reliable data on rainfall. To carry out a correct evaluation of water resources, both in the small and large scale, disposing hydrological networks that involve a certain number of measuring devices becomes critical. Despite the great amount of studies that have been developed on measuring devices such as rain gauges, there are still many errors that remain in the measurements and that have not been ruled out yet, thus affecting the accuracy of the measurements. In this sense, the design of a device that provides an accurate measurement of rainfall and also results affordable, could be the key to a product with great acceptance in the market. The aim of this work is to present the design of a measurement device that provides accurate data and can be used in multiple ways: as an ordinary rain gauge, as a rain gauge recorder, or even allowing to carry on both functions simultaneously. The methodology followed for its implementation has consisted in analyzing the techniques and procedures to be trailed at quantifying rainfall, conducting a market study and analyzing specifications to be in accordance to WMO (World Meteorological Organization) [2] [3] to then go through a conceptual design and finally complete the detailed design where materials are valued and simulation tests are performed in order to meet certain accuracy and economical requirements.
Keywords: Diseño técnico; Rain gauge; Accuracy requirements; Economical requirements; Device design